PENGALAMAN PSIKOLOGIS NARAPIDANA NARKOBA DAN IMPLIKASINYA TERHADAP IMPLEMENTASI KONSELING SUFISTIK - Tajiri, Hajir (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
A person's falling into drug abuse, consuming and distributing them, is an action that is categorized as a crime. The consequence is that those caught by the authorities have to spend time in a correctional institution, an institution that is not only prison but also rehabilitation. This research aims to reveal the psychological experiences of prisoners and the application of Sufistic counseling by the UIN Sunan Gunung Djati community service team. The research method used is descriptive with a qualitative approach. The key informants for this research were the prison head, supervisor or counselor and 10 prisoners who were selected purposively with the consideration that the ten prisoners could be met and interviewed when they took part in religious activities at the mosque. The collected data is processed, interpreted and analyzed qualitatively. The research results show that the prisoners have a strong desire to change, especially because of feelings of deterrence while in prison, but they admit that it is difficult to escape drug addiction. Their need for Sufistic counseling lies in the need to strengthen their consciousness when they want to stop illegal behavior, ensuring calm and certainty while living a righteous life. The application of Sufistic counseling is oriented towards fulfilling spiritual needs which become strength in repelling the challenges faced. Sufistic counseling that is able to generate a deep understanding of the true nature of life that must be lived.